Improvement of Commercial Active Carbon for Use in an Adsorption Cooling System - B. Buczek; L. Czepirski; E. Komorowska-Czepirska (Adsorption Science & Technology)
Of the various gas/solid adsorption processes, the adsorption of methanol on active carbon seems to be most interesting for use in thermodynamic systems such as heat pumps and transformers, as well as in cooling systems. The porous structures of two series of active carbons modified by the successive removal of the external layers from the particle surface, one by abrasion in a spouted bed and the other by subsequent demineralization of the abraded particles, were evaluated on the basis of nitrogen and methanol adsorption data. The porous structure parameters for these two sorbate series agreed reasonably well and allowed the D–R approach to be usefully applied for the characterization of these systems. The methods for calculating the heat effects associated with methanol adsorption over wide ranges of temperature and pressure are discussed.